PENINGKATAN KETERAMPILAN BERKOMUNIKASI VERBAL DAN NONVERBAL DALAM STORYTELLING SISWA SMP DOREA GUNUNGSINDUR - Sudarja, Kusman; Situmorang, Komilie; Purwanti, Christina; Hananto, Hananto; Suteja, Hanna (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Communication skills in Indonesian and English are crucial aspects for students in the current information era. Indonesian and English languages are taught from elementary school to university as an integral part of the curriculum, with competence evaluated through formative and summative assessments in class. To enhance language proficiency, particularly in verbal and nonverbal communication skills, lecturers from the Indonesian Language and English Language departments of FoN (Faculty of Science) and TC (Teacher's College) will organize workshops and competitions at SMP Kristen Dorea Gunungsindur. These activities include storytelling and competitions focusing on English vocabulary mastery. The main objective is not only to assess language skills but also to train students in both verbal and nonverbal communication aspects, aiming to enhance their resilience and positive competitiveness. It is expected that active participation in these workshops and competitions will further motivate students to sharpen their skills in Indonesian and English languages. Keywords: verbal and nonverbal communication skills, storytelling, vocabulary mastery